PERANCANGAN KAMPANYE SOSIAL TENTANG PENINGKATAN SELF-ESTEEM DALAM MENANGGULANGI STEREOTIPE NEGATIF STANDAR KECANTIKAN FISIK BAGI PEREMPUAN (studi kasus Kota Batam) - Sherinne Chaerunnisa; Muhammad Adi Sukma Nalendra (JURNAL RUPA MATRA, 2023)
Social media, advertisements, films, and other forms of media often portray women with smooth, white skin, and ideal bodies, giving the perception of beauty standards for women. The comparison with these standards can decrease self-confidence and have negative impacts on women's mental well-being, such as the inability to accept themselves, feeling sad, ashamed, and afraid to interact. A social campaign is required to increase self-esteem in women. The campaign aims to educate women that true beauty is when they recognize themselves, know their qualities, and value them. Moreover, the social campaign also provides important educational benefits for women to understand that true beauty is not just about physical appearance, but also the values within themselves that need to be cherished and maintained.